2017
DOI: 10.1093/ckj/sfx094
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for imaging-based diagnosis and management of renal angiomyolipoma associated with tuberous sclerosis complex

Abstract: Renal angiomyolipomas are found in up to 80% of tuberous sclerosis complex (TSC) patients. Although these tumours are usually asymptomatic, lesions >3 cm in diameter are prone to bleeding and up to 10% of TSC patients may experience a massive and potentially fatal retroperitoneal haemorrhage. Diagnosis can be complicated because of the initial lack of symptoms and the fat-poor content of atypical renal angiomyolipomas. After diagnosis, tumour growth and the emergence of new tumours must be monitored. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
1
25
0
2
Order By: Relevance
“…All eleven TSC-patients in the present study had, at any time, an intervention compared to 61% in the group with sporadic AML. Other authors have reported on a more aggressive course of the AML-disorder in TSCpatients [4]. The eleven patients in our study had in all 13 retroperitoneal bleeding episodes, two episodes of hematuria and five cases of progress in size, leading to 22 AE and three nephrectomies.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…All eleven TSC-patients in the present study had, at any time, an intervention compared to 61% in the group with sporadic AML. Other authors have reported on a more aggressive course of the AML-disorder in TSCpatients [4]. The eleven patients in our study had in all 13 retroperitoneal bleeding episodes, two episodes of hematuria and five cases of progress in size, leading to 22 AE and three nephrectomies.…”
Section: Discussionmentioning
confidence: 51%
“…There are two major varieties of renal AML, one associated with tuberous sclerosis complex (TSC) and one sporadic form. Renal AML associated with TSC are often multiple, bilateral, symptomatic and without male or female predominance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Potential risks, such as prolonged sedation or excessive examination time, must be considered when deciding to perform kidney MRI. In patients with AML 3 cm or larger, yearly repeat MRI has been recommended (74). In patients without AMLs at initial MRI, this group suggests annual US for follow up, with repeat MRI every 2-3 years.…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 99%
“…In total, 60-80% of TSC patients suffer from renal manifestations of aberrant cell growth and dysregulated cell proliferation, resulting in renal cysts and hamartomatous renal tumors such as angiomyolipomas 1,5,6 . Such renal lesions can cause kidney enlargement and tubulointerstitial fibrosis, leading to impaired renal function and/or angiomyolipomaassociated hemorrhage 7,8 . Although more than half of TSC patients fail to be diagnosed at the early stage of this disease, with innovative detection technologies, more and more TSC patients are diagnosed with kidney pathology 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mTORC1 is considered a pharmacological target for the treatment of TSC 7,10 . Unfortunately, mTORC1 inhibitors currently used in the clinic seemed to only have a limited cytostatic effect, as the TSC tumors grew again after mTORC1 inhibitors were discontinued, and long-term mTORC1 inhibition could cause detrimental side effects [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%